Why Does Separation Distress Hurt? Comment on MacDonald and Leary (2005). [article]. - Panksepp, Jaak
Evidence is substantial that separation-distress circuity in animal model is related intimately to opiod-sensitive pain regulatory systems of the brain . The evidence that basic pain-affect mechanisms are integral to the feelings of defensive fear anxiety and aggression is modest . Although anger and anxiety can be reduced by opiates, the effects are not as robust and specific as those observed with the low doses that quell separation distress. The role of " social pain" maybe larger for the affective underpinnings of jealousy, shame, and guilt (all variants of social exclusion and abandonment) than for fear and aggression. Interdisciplinary insights might be facilitated by more forthright analyses of how affective states are created within the brain. This will require better dialogued between behavioral neuroscientists and the rest of psychology interested in foundational psychoevolutionary issues. -- (from the author).